-5(x+2)+8x=-2+3x-8

Simple and best practice solution for -5(x+2)+8x=-2+3x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+2)+8x=-2+3x-8 equation:


Simplifying
-5(x + 2) + 8x = -2 + 3x + -8

Reorder the terms:
-5(2 + x) + 8x = -2 + 3x + -8
(2 * -5 + x * -5) + 8x = -2 + 3x + -8
(-10 + -5x) + 8x = -2 + 3x + -8

Combine like terms: -5x + 8x = 3x
-10 + 3x = -2 + 3x + -8

Reorder the terms:
-10 + 3x = -2 + -8 + 3x

Combine like terms: -2 + -8 = -10
-10 + 3x = -10 + 3x

Add '10' to each side of the equation.
-10 + 10 + 3x = -10 + 10 + 3x

Combine like terms: -10 + 10 = 0
0 + 3x = -10 + 10 + 3x
3x = -10 + 10 + 3x

Combine like terms: -10 + 10 = 0
3x = 0 + 3x
3x = 3x

Add '-3x' to each side of the equation.
3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 9x-139=3x-13 | | -6(2+x)=4-8x | | (4x)=(x+120) | | 3(2x-7)-7(x-8)=x-7-6+4x | | (1+c^2)(4c^2+7c-3)=0 | | 15-(-4)=x | | 6(2x-9)=4+11x | | 18/7.5=x/5 | | 3x-y+z=1 | | -3x-5=6x-32 | | 13=2y-3y+4 | | 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 | | -3x^2+11x+25=0 | | 2x-1+6x=28 | | y=2x(4+3)-2 | | -11+z=6(z-4) | | 9v^2-121f^2= | | -7-2x-x=2 | | -6(1+3k)=-36-3k | | 2x^2-30x+75=0 | | x+6+2x=-x-4-2 | | 10p+4=-3+7p+1p | | -6(2x-3)+15=36 | | 9a^2+42at+49t^2= |

Equations solver categories